Mechanism of orthotic therapy for the painful cavus foot deformity - Najafi, Bijan (BioMed Central, 2014)
BACKGROUND: People who have extremely high arched feet or pes cavus often suffer from substantial foot pain. Custom-made foot orthoses (CFO) have been shown to be an effective treatment option, but their specificity is unclear. It is generally thought that one of the primary functions of CFO is redistributing abnormal plantar pressures. This study sought to identify variables associated with pain relief after CFO intervention. METHODS: Plantar pressure data from a randomized controlled trial of 154 participants with painful pes cavus were retrospectively re-analyzed at baseline and three month post CFO intervention. The participants were randomized to a treatment group given CFO or a control group given sham orthoses. RESULTS: No relationship between change in pressure magnitude and change in symptoms was found in either group. However, redistribution of plantar pressure, measured with the Dynamic Plantar Loading Index, had a significant effect on pain relief (p = 0.001). Our final model predicted 73% of the variance in pain relief from CFO and consisted of initial pain level, BMI, foot alignment, and changes in both Dynamic Plantar Loading Index and pressure–time integral. CONCLUSION: Our data suggest that a primary function of effective orthotic therapy with CFO is redistribution of abnormal plantar pressures. Results of this study add to the growing body of literature providing mechanistic support for CFO providing pain relief in painful foot conditions. The proposed model may assist in better designing and assessing orthotic therapy for pain relief in patients suffering painful cavus foot deformity. TRIAL REGISTRATION: Randomized controlled trial: ISRCTN84913516